Integration of Corporate Performance Theory, Resource-Based View, Resource Dependency, Dynamic Capabilities, and Social Cognitive Theory in Enhancing the Competitiveness of SMEs in Indonesia - Nur Endah Sabarini; Yayan Hendayana (Dinasti Publisher, 2025)
This study aims to explore the integration of corporate performance theory, Resource-Based View (RBV), Resource Dependency Theory (RDT), Dynamic Capabilities Theory (DCT), and Social Cognitive Theory (SCT) in enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. MSMEs face various challenges, including limited innovation, restricted access to financing, low digital competencies, dependence on external resources, and insufficient adaptive capabilities. This research employs a systematic literature review method, collecting, classifying, and analyzing recent relevant literature, including journals, research reports, and academic publications, to develop an integrative conceptual framework. The findings indicate that optimizing internal resources through RBV, managing external dependencies through RDT, developing adaptive capabilities through DCT, and enhancing individual self-efficacy and social learning through SCT collectively contribute to improving MSME performance and competitiveness. The study recommends strategies such as strengthening internal capacities, fostering external collaborations, adopting technology, and implementing integrated policy support. These findings provide both theoretical and practical foundations for policymakers and MSME actors to achieve sustainable competitive advantages and guide future empirical research focused on MSME development in Indonesia.